EKSISTENSI HAK KEBENDAAN DALAM PERSPEKTIF HUKUM PERDATA BW - Suryantoro, Dwi Dasa (Universitas Nurul Jadid, 2023)
Substantive rights in terms of civil law, substantive rights are absolute rights over an object, which gives direct control over an object, which can be defended against anyone, and which cannot be protected by the object against other people. For example, property/ownership rights, mortgages, mortgages, trustees, and other collateral rights and titles. In the current civil law system in Indonesia, substantive rights guaranteed by the distinction between property rights are divided into movable and immovable property. What is meant by separation of personal and immovable property is very important in relation to security devices. These differences in objects are used to determine the type of guarantor/loan guarantee that can be assigned to a given loan.Keywords: Property Rights, and Civil Law